Becoming a hoax buster in WhatsApp groups as an effort to limit the dissemination of misleading health information - Suminar, Jenny Ratna; Hadisiwi, Purwanti (Jurnal Studi Komunikasi, 2021)
The dissemination of hoax information, especially about health, is spread quickly and massively through WhatsApp Group. The use of WhatsApp Group makes it easy to share and distribute information. This study raised Hoax Buster’s phenomenon, which is someone who checks the facts at WhatsApp Group. This study explored the answers to the following questions: how WhatsApp Group members act as Hoax Buster, reasons for being a Hoax Buster, and how Hoax Buster develops communication patterns. This research used a qualitative method with case studies where data was obtained through observation and in-depth interviews with several sources. The results of the study were: 1) The existence of Hoax Buster is due to the circulation of Hoax in WhatsApp Group, 2) The role of Hoax Buster arises because of concerns about health Hoaxes in WhatsApp Group and encourages WhatsApp Group members not easily to believe unclear information, 3) Hoax busters communicate through several stages